Decoupling stability and release in disulfide bonds with antibody-small molecule conjugates. Issue 1 (30th August 2016) - Pillow, Thomas H.; Sadowsky, Jack D.; Zhang, Donglu; Yu, Shang-Fan; Del Rosario, Geoffrey; Xu, Keyang; He, Jintang; Bhakta, Sunil; Ohri, Rachana; Kozak, Katherine R.; Ha, Edward; Junutula, Jagath R.; et al.
Abstract : A novel bioconjugation strategy utilizes a disulfide bond to site-specifically couple a small molecule drug to an antibody, enabling both high circulation stability and quick intracellular release. Abstract : Disulfide bonds provide a bioactivatable connection with applications in imaging and therapy. The circulation stability and intracellular release of disulfides are problematically coupled in that increasing stability causes a corresponding decrease in cleavage and payload release. However, an antibody offers the potential for a reversible stabilization. We examined this by attaching a small molecule directly to engineered cysteines in an antibody. At certain sites this unhindered disulfide was stable in circulation yet cellular internalization and antibody catabolism generated a disulfide catabolite that was rapidly reduced. We demonstrated that this stable connection and facile release is applicable to a variety of payloads. The ability to reversibly stabilize a labile functional group with an antibody may offer a way to improve targeted probes and therapeutics.